European integration and the case for compensatory regional policy - Christiane Krieger-Boden (European Regional Science Association (ERSA), 2002)
The ongoing process of European integration is likely to increase trade and factor mobility thereby increasing interregional competition and affecting the interregional division of labour. From a theoretical standpoint, particularly on the basis of the New Economic Geography (NEG), rising specialization and polarization of European regions could result from this process, and could entail a growing core-periphery-divide of regional income. Hence, there may be winning and losing regions of the integration process, according to the way industrial concentration and regional specialization takes place. Such an supposition evokes questions on the need of an accompanying compensatory regional policy, and whether it can be justified from an efficiency and/or distributional perspective. Also, questions arise as to the adequate design of such compensatory regional policy, with respect to institutions, measures, and recipients. The proposed paper will start reviewing the case for regional policy in Europe on theoretical and empirical grounds. It will then discuss some options for an efficient European regional policy, and compare it to the actual EU regional policy.
Keywords: 330